Keeper of the lost cities: Keeper of the Lost Cities # 1 Part 1 : the graphic novel. - Messenger, Shannon; Frenn, Celina; Chianello, Gabriella; Messenger, Shannon (New York : Aladdin, 2023)
A graphic novel adaptation of the book, in which twelve-year-old Sophie discovers the abilities that have always caused her to stand out are because she is actually an elf and, after she is brought to Eternalia where she can hone her skills, Sophie learns she harbors certain secrets that others would kill to learn.
Based on: Keeper of the lost cities (2012) / by Shannon Messenger.
Chiefly illustrations.
new kids book 2023 winter.
Keywords: Ability -- Comic books, strips, etc; Psychic ability -- Comic books, strips, etc; Memory -- Comic books, strips, etc; Identity (Psychology) -- Comic books, strips, etc; Foster parents -- Comic books, strips, etc; Elves -- Comic books, strips, etc; Fantasy comic books; Graphic novels